Analisis Keanekaragaman Hayati: Peluang Agroforestri dalam Mengatasi Perubahan Iklim di Dulamayo, Gorontalo, Indonesia - Hiola, Abdul Samad; Sandalayuk, Daud; Ruruh, Alexander (PT. Banjarese Pacific Indonesia, 2024)
The challenges posed by climate change and the decline of biodiversity to the sustainability of global agricultural systems are serious.Agroforestry has emerged as a strategy with the potential to enhance the resilience of agricultural systems while conserving biodiversity amidst the threats of climate change.This study aims to evaluate the potential of agroforestry to enhance biodiversity and the resilience of agricultural systems to climate change in Dulamayo, Gorontalo. The research methodology is based on vegetation analysis and the calculation of biodiversity indices, with data collection encompassing measurements of tree characteristics and species identification.The results indicate the presence of 17 tree species with a total of 154 individuals, where Candlenut (Aleurites molucana) and Sugar Palm (Arenga pinnata) dominate with proportions of 22.73% and 20.13%, respectively. The Shannon-Wiener diversity index yielded a moderate value (H' = 2.311) with a high evenness level (E = 0.816), indicating a high ecosystem stability.The findings suggest that the agroforestry system in Dulamayo plays a crucial role in supporting biodiversity and the resilience of ecosystems to climate change through its complex and diverse vegetation structure.